Environment assisted electron capture - Gokhberg, Kirill; Cederbaum, Lorenz S. (Journal of physics. Conference Series, 2012)
Electrons scattering off isolated atoms or positive atomic ions may be captured in the non-resonant photorecombination or resonant dielectronic recombination processes with the excess energy carried off by a photon. We demonstrate that in a medium a new interatomic process becomes important, where in the electron capture by an atom or atomic ion the energy is transferred to a neigbouring species ionising it. We discuss different manifestations of this interatomic Coulombic electron capture and estimate its efficiency for a number of realistic systems.